2023
DOI: 10.1093/jnci/djad268
|View full text |Cite
|
Sign up to set email alerts
|

The impact of multidisciplinary cancer conferences on overall survival: a meta-analysis

Ryan S Huang,
Andrew Mihalache,
Abdulwadud Nafees
et al.

Abstract: Background Multidisciplinary cancer conferences (MCCs) are comprised of regular meetings between diverse specialists working together to share clinical decision making in cancer care. The aim of this study is to systematically review and meta-analyze the effect of MCC intervention on overall survival of cancer patients. Methods A systematic literature search was conducted on Ovid MEDLINE, EMBASE and the Cochrane Controlled Re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 82 publications
0
2
0
Order By: Relevance
“…Nonetheless, MTBs can improve overall survival by up to 11.2 months, and no cancer patient should be withheld from this benefit. 10 Our model is proof that calculated and coordinated interventions can improve cancer care, even with the slightest of resources.…”
mentioning
confidence: 58%
“…Nonetheless, MTBs can improve overall survival by up to 11.2 months, and no cancer patient should be withheld from this benefit. 10 Our model is proof that calculated and coordinated interventions can improve cancer care, even with the slightest of resources.…”
mentioning
confidence: 58%
“…Huang et al [ 10 ] conducted a meta-analysis report elucidating the influence of multidisciplinary cancer conferences on overall survival. The study revealed a median survival time of 30.2 months in the multidisciplinary cancer conference group, contrasting with 19 months in the control group [ 10 ].…”
Section: Discussionmentioning
confidence: 99%